Study of burn injuries and pattern with seasonal variation in a tertiary care centre - Verma, Kush; Thakurani, Sangeeta; Negi, Ravikanta; Shah, Deepti (International Surgery Journal, 2023)
Background: Burn injuries pose a significant public health concern, necessitating a detailed investigation to enhance injury prevention strategies. This study investigates the distribution and patterns of burn injuries in a tertiary care centre, focusing on gender, age, burn types, outcomes, and seasonal variations. Methods: Data from a multi-year retrospective analysis (2018-2022) were collected and analysed to determine the gender distribution of burn incidents. Additionally, age distributions were examined to understand the prevalence of burns across different age groups. Burn types were classified into flame, scald, electric, and chemical/miscellaneous, while outcomes were categorised as discharged, abscond/LAMA (left against medical advice), death, or transfer to other departments. The study also investigated the seasonal variations in scald and flame burn incidents. Results: The highest gender disparities were observed in 2018 and 2019, with 748 and 661 male cases, respectively, compared to 355 and 345 female cases. Children aged 1-10 constituted the largest burn cases, followed by individuals aged 25-40. Flame burns were the most common, accounting for the highest number of cases throughout the study period. Scald burns ranked second, followed by electric and chemical/miscellaneous burns. Most burn incidents resulted in discharge, followed by abscond/LAMA cases. Deaths and transfers to other departments were less frequent outcomes. The number of discharged cases increased gradually over the study period, indicating positive treatment outcomes. Conclusions: The conclusions emphasize the necessity for all-encompassing preventative initiatives, including public awareness campaigns, safety education, and interventions for vulnerable groups.